2021
DOI: 10.1111/jop.13264
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment neutrophil‐to‐lymphocyte ratio is an independent prognostic factor in head and neck squamous cell carcinoma: Meta‐analysis and trial sequential analysis

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer in the world, with 890 000 new cases and 450 000 deaths in 2018 worldwide. 1 Despite improvements in research and therapy made in the last decades, survival has not significantly improved and the 5 years overall survival (OS) rate is still less than 50%. 2 Classic prognostic factors are not sufficient to predict patients' prognosis, due to the heterogeneity of molecular mechanisms and tumour behaviours related to HNSCC. For these rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 89 publications
3
22
1
Order By: Relevance
“…In addition, high fibrinogen and high NLR were found to be important indicators for predicting clinical outcome in this study ( P < 0.001 and P = 0.008). The results of our study are consistent with those of previous meta-analyses, showing that high NLR significantly reduces the survival time of head and neck squamous cell carcinoma patients [ 28 ]. We propose the following mechanism of action: Fibrinogen may function by forming a protective framework that facilitates tumor migration, invasion, and angiogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, high fibrinogen and high NLR were found to be important indicators for predicting clinical outcome in this study ( P < 0.001 and P = 0.008). The results of our study are consistent with those of previous meta-analyses, showing that high NLR significantly reduces the survival time of head and neck squamous cell carcinoma patients [ 28 ]. We propose the following mechanism of action: Fibrinogen may function by forming a protective framework that facilitates tumor migration, invasion, and angiogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, NLR could be used as an independent prognostic indicator in patients with OSCC [ 27 ]. A recent meta-analysis of 17 studies with 4597 patients showed that pre-treatment NLR correlates with a statistically significant decrease of OS in head and neck squamous cell carcinoma patients [ 28 ]. The generation of inflammatory cytokines/chemokines by neutrophils facilitates the occurrence and development of tumors by creating a suitable tumor microenvironment [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the over-regulation of miR-21 [ 7 , 8 ], miR-155 [ 9 ], and miR-31 [ 10 ] would be associated with a worse prognosis, and among the downregulated is reported miR-195 [ 11 ]. Confirmation of these data also comes from recent systematic reviews with meta-analysis, conducted on the prognostic value of these groups of microRNAs [ 12 ]. In a similar way, more miRs are associated with a possible use as a prognostic biomarker of survival in HNSCC, and among these were recently highlighted the miR-196a and the miR-196b [ 13 ].…”
Section: Introductionmentioning
confidence: 64%
“…The idea of to diagnose cancer through simple routine laboratory tests with a little amount of blood samples is worthy of investigation for many researchers. Some inflammatory markers including lymphocyte to monocyte ratio, neutrophil to lymphocyte ratio, albumin to globulin ratio were described previously , however, majority of these studies aimed to evaluate only the prognostic significant of the aforementioned markers in different cancer types (Stotz et al, 2014;Jia et al, 2015;Gu et al, 2016;Hsueh et al, 2017;Tan et al, 2018;Song et al, 2021;Tezuka et al, 2021;Atsumi et al, 2021;Castineiras et al, 2021;Mariani et al, 2022). There were a only a few studies had been published about association between systemic inflammatory markers and prediction of cancer diagnosis (Kocer et al, 2015;Li et al, 2017;Ataş et al, 2021) .…”
Section: Discussionmentioning
confidence: 99%